No Master of Himself: Pope and the Response of Wonder - Playfair Quinsey, Katherine (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2020)
Although he is the exemplar of poetic balance, control, and precision, Pope’s classical aesthetics and ecological vision are ultimately authorized not by restraint but by excess, by a response of wonder: emotive not rational, imaginative not formulaic, and fundamentally religious in nature. Pope’s lifelong and profound engagement with wonder—in both personal expression and formal poetics—embodies the tensions of his time: between myth and parody, enthusiasm and restraint, hyperbolic parody and interrupted awe, self-realization and self-loss, emotive expression and formalistic control. His poetry continually evokes the response of wonder, pushing at the boundaries of verse satire, and embodied through his mastery of the couplet. Wonder in Pope’s writings is specifically associated with admiration for the supranatural, with release from the limitations of the body, and with a sweeping environmental vision. Finally, the ideas of “stupefaction” and “rapture” appear throughout Pope’s work in a paradoxical expansion and distancing of perspective, with the perpetual fear of the loss of the observing self.